Real-Time Concepts for Embedded Systems - Li (Qing); Yao (Caroline) ("CMP Media LLC, 1601 West, 23rd Street, Suite 200 Lawrence, Kansas-66046", 2006)
System Analysis and Design
22.5
Keywords: System Analysis and Design